(untitled) (American Journal of Business Management, Economics and Banking, 2022)
This study dealt with the practices of strategic thinking as an independent variable with its sub-dimensions represented by (strategic intent, holistic thinking, leading assumptions, and thinking in time) and organizational success represented by (resources, structure, management, process, knowledge management) and University of Thi-Qar affiliated to the Ministry of Education was chosen. Higher education and scientific research in Iraq to be the study community and to achieve the objectives of the research, a questionnaire was developed and distributed to (170) individuals, of which only (125) were returned for use,. a percentage of (74%). Represented by the senior leaders who are at the rank of dean of the faculty, scientific and administrative assistant, department head, directors of centers and research, and people’s officials in all facilities and faculties of Thi Qar University, because they are interested and specialized in strategic thinking practices and responsible for achieving organizational success at the university, and with the aim of data processing, many statistical methods were used using the statistical program (AmosV&Spss. 23) to come up with a scientific outcome within the framework of this important topic, and the researcher reached a number of conclusions, the most important of which was (the existence of a quest by the senior management in the College of Administration and Economics in applying mechanisms that will achieve organizational success by working according to the adoption of practices and concepts of modern strategic thinking). The most prominent recommendations were (the necessity of developing functional work paths to attract and develop distinguished individuals in strategic thinking towards the formation of strategic human capital in developing the overall performance of the organization).